Histone deacetylase 10 promotes autophagy-mediated cell survival - Oehme, Ina; Linke, Jan-Peter; Böck, Barbara; Milde, Till; Lodrini, Marco; Hartenstein, Bettina; Rettig, Inga Edeltraud; Eckert, Christian; Roth, Wilfried; Kool, Marcel; Kaden, Sylvia; Gröne, Hermann-Josef; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2013)
Tumor cells activate autophagy in response to chemotherapy-induced DNA damage as a survival program to cope with metabolic stress. Here, we provide in vitro and in vivo evidence that histone deacetylase (HDAC)10 promotes autophagy-mediated survival in neuroblastoma cells. We show that both knockdown and inhibition of HDAC10 effectively disrupted autophagy associated with sensitization to cytotoxic drug treatment in a panel of highly malignant V-MYC myelocytomatosis viral-related oncogene, neuroblastoma derived-amplified neuroblastoma cell lines, in contrast to nontransformed cells. HDAC10 depletion in neuroblastoma cells interrupted autophagic flux and induced accumulation of autophagosomes, lysosomes, and a prominent substrate of the autophagic degradation pathway, p62/sequestosome 1. Enforced HDAC10 expression protected neuroblastoma cells against doxorubicin treatment through interaction with heat shock protein 70 family proteins, causing their deacetylation. Conversely, heat shock protein 70/heat shock cognate 70 was acetylated in HDAC10-depleted cells. HDAC10 expression levels in high-risk neuroblastomas correlated with autophagy in gene-set analysis and predicted treatment success in patients with advanced stage 4 neuroblastomas. Our results demonstrate that HDAC10 protects cancer cells from cytotoxic agents by mediating autophagy and identify this HDAC isozyme as a druggable regulator of advanced-stage tumor cell survival. Moreover, these results propose a promising way to considerably improve treatment response in the neuroblastoma patient subgroup with the poorest outcome.
Gesehen am 29.11.2021